Distribution Characteristics of SOC, STN, and STP Contents Along a Slope Aspect Gradient of Loess Plateau in China - Liu, Minxia; Yu, Ruixin; Li, Liang; Xu, Lu; Mu, Ruolan; Zhang, Guojuan (Frontiers in Soil Science, 2021)
In this study, the effects of slope aspects and depths on soil organic carbon (SOC), soil total nitrogen (STN), and soil total phosphorus (STP) were quantified in disturbed restoration regions of Gaolan County, located in the Gansu Province of semi-arid loess Plateau of China. Soil samples were collected at 0–10, 10–20, 20–40, 40–60, 60–80, and 80–100 cm on southern, southwestern, western, northwestern, and northern slope aspects of three hills. A total of 75 soil profiles and 450 soil samples were analyzed. Results showed that the SOC, STN, and STP content varied from 1.65 to 12.87 g/kg, 0.45 to 1.53 g/kg, and 0.07 to 0.78 g/kg, and the SOCD, STND, and STPD at 0–100 cm varied from 3.9 to 9.5 kg/m2, 0.58 to 1.35 kg/m2, and 0.33 to 0.56 kg/m2, which increased from the southern to northern slope aspects. The SOC, STN, and STP contents and SOCD, STND, and STPD were mainly in the 0–60 and 60–100 cm soil layers. The vertical descent rate was γSOC > γSTN > γSTP for both content and density. For a single soil nutrient, the decline rate of its content and density on the northern slope aspect was greater than that on the southern slope aspect, that is γN > γ All > γS. The correlation degree between soil properties and SOC and STN content were above 0.6, the overall correlation with STP content was <0.6. These results confirmed that topography (slope aspects) was the most significant factor controlling the distribution patterns of SOC, STN, and STP in hill ecosystems. Overall, the northern slope aspect (vs. southern slope aspect) was more favorable to the preservation of SOC, STN, and STP. Accordingly, in the Loess Plateau and similar fragile environments, soil nutrient protection and vegetation restoration are selective to some extent.